Tetraploid Teak Seedling was More Tolerant to Drought Stress than Its Diploid Seedling - Ridwan; Tri Handayani; Indira Riastiwi; Witjaksono (Foresty Faculty of Hasanuddin University, 2018)
The demand of teak (Tectona grandis L.f.) wood for the national industry can only be fulfilled about 0.75 million m3/year from 2.5 million m3/year which is caused by the long of harvesting time and the derivation of suitable land for teak due to climate change. Indonesia has a wide area of dry land to develop teak plant, so that, fast growing and drought resistant teak seedling is needed. The aim of this research was to compare the resistance of tetraploid and diploid teak clone to drought stress. The research was conducted in the greenhouse using Randomized Block Design with two factors and 9 replications. The first factor was clone i.e. diploid (2x) and tetraploid (4x). The second factor was drought stress levels consisted of 5 watering intervals i.e. 3 days, 7 days, 14 days, 21 days, and watering only at the treatment began. Plant height, stem diameter, number of leaves, leaf area, leaf thickness, leaf water potential, stomata, root system, and plant dry weight were observed to evaluate the plant growth. The result showed that the growth of both tetraploid and its diploid seedling clones were declined under drought stress. However, the growth of tetraploid seedling is better than its diploid seedling.